2012
DOI: 10.1134/s1063780x12010060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flux surface curvature on the linear coupling of electron cyclotron waves in tokamak plasmas

Abstract: Specific features of the linear interaction of ordinary and extraordinary electromagnetic waves in the electron cyclotron frequency range in a nonuniform plasma confined in a toroidal magnetic trap are con sidered. Reduced wave equations taking into account the curvature of the cut off surfaces in toroidal geom etry are formulated. Using these equations, the distributions of the wave fields in the coupling region are ana lyzed. A method for calculating quasi optical beams passed through the region of linear wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…The necessary condition for the applicability of the approximation of plane flat cutoff surfaces is the condition that the beam is insignificantly contributed by the modes with λ n λ cr that do not correspond to the plane cutoff approximation. There are several ways to satisfy this condition; a detailed study may be found in [17]. Here we consider the case most relevant for fusion applications in which the original incident beam consists of localized modes with λ n < λ cr that fit the 'parabolic' well, and contribution of other modes to the spectrum is negligibly small.…”
Section: Interaction Of Two Mode-coupling Regions and Correspondence ...mentioning
confidence: 99%
“…The necessary condition for the applicability of the approximation of plane flat cutoff surfaces is the condition that the beam is insignificantly contributed by the modes with λ n λ cr that do not correspond to the plane cutoff approximation. There are several ways to satisfy this condition; a detailed study may be found in [17]. Here we consider the case most relevant for fusion applications in which the original incident beam consists of localized modes with λ n < λ cr that fit the 'parabolic' well, and contribution of other modes to the spectrum is negligibly small.…”
Section: Interaction Of Two Mode-coupling Regions and Correspondence ...mentioning
confidence: 99%
“…As noted in [21][22][23], the curvatures of the magnetic field lines and toroidal magnetic surfaces can contribute to the coupling efficiency in the same way as the fluctuations. Their influence can also be roughly estimated through the redefined parameter K y in (18) as…”
Section: Comparison With the Curvature Effectsmentioning
confidence: 88%
“…On the other hand, such an assumption is certainly not satisfied for toroidal devices except for the special case of the equatorial launch of microwave radiation. For a regular toroidal plasma, it is known that the non-one-dimensional geometry of the coupling region leads to qualitatively new physical effects [16][17][18], which under certain conditions can substantially influence the O-X mode coupling efficiency [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation